Pathological phenomena not classified as mobbing – de lege ferenda postulates - Fonderska , Magdalena; Pietrzak, Damian (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
The aim of the study is to examine the applicable legal regulations on mobbing in relation to the evolving forms provision of work and other pathological phenomena not classified as mobbing. The starting point for the considerations is the definition of mobbing contained in the applicable provisions of labor law. Personal rights were also subjected to a detailed analysis, the violation of which may be the basis for pathological behavior not classified as mobbing.